2014
DOI: 10.21161/mjm.58013
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and antiviral activity of Marrubium vulgare

Abstract: Aims:The present study is to investigate the phytochemical content, cytotoxicity and antiviral activity of the crude and fractions from Marrubium vulgare. Methodology and results:The crude methanol extract and fractions using hexane, chloroform, ethyl acetate and nbutanol of M. vulgare whole plant were produced in this study. Qualitative phytochemical analysis revealed the presence of flavones aglycones and steroid in all preparations except for the hexane fraction. Carbohydrates, saponins were found present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…Similarly, the presence of secondary metabolites including flavonoids, tannins, mucilages, sterols and triterpenes, coumarins, and saponins were confirmed, however, alkaloids were found to be absent ( Table 4 ). Interestingly, the results of this study are consistent with those of Akther et al and Fayyad et al who reported in their study that M. vulgare is rich in gallic tannins, catechin tannins, sterols, and triterpenes and flavonoids ( Akther et al, 2013 ; Fayyad et al, 2014 ). Tannins and flavonoids are widely explored for their pharmacological properties including antioxidant, antiviral, antitumor, anti-inflammatory, anti-allergic and anti-cancer activities ( Khanbabaee and van Ree, 2001 ; Crozier et al, 2009 ).…”
Section: Resultssupporting
confidence: 93%
“…Similarly, the presence of secondary metabolites including flavonoids, tannins, mucilages, sterols and triterpenes, coumarins, and saponins were confirmed, however, alkaloids were found to be absent ( Table 4 ). Interestingly, the results of this study are consistent with those of Akther et al and Fayyad et al who reported in their study that M. vulgare is rich in gallic tannins, catechin tannins, sterols, and triterpenes and flavonoids ( Akther et al, 2013 ; Fayyad et al, 2014 ). Tannins and flavonoids are widely explored for their pharmacological properties including antioxidant, antiviral, antitumor, anti-inflammatory, anti-allergic and anti-cancer activities ( Khanbabaee and van Ree, 2001 ; Crozier et al, 2009 ).…”
Section: Resultssupporting
confidence: 93%
“…Según Amal Gaber et al (2014), los terpenos tienen la capacidad de interrumpir la adhesión del virus a la superficie de las membranas celulares del hospedero, así como de inhibir la replicación del genoma viral.…”
Section: Compuestosunclassified
“…Foam index equal 550, in accordance with, 18 our results indicate that Moroccan Marrubium vulgare L. contains saponins in its leaves. Several studies have reported the presence of saponins in Marrubium vulgar L. 13,27 Extraction of Saponins Three different methods were used to extract saponins. Each extract yield is calculated from dry weight of Marrubium vulgare L. leaves.…”
Section: Saponins Characterizationmentioning
confidence: 99%
“…11 The aerial part of the Marrubium vulgare L. contains several secondary metabolites, the most interesting ones arepolyphenols, flavonoides, tannins, terpenoids, 5 marrubiin, phenolic acids, phenylpropanoid glycoside, 6 and saponins. 12,13 Saponins are bioactive compounds with potential health benefits. Besides their role in plant defense, they are considered to have anti-cancer, anti-inflammatory, antibacterial and antifungal activities, 14 and the antioxidant activity, 15,16 protection against allergies, platelet aggregation, hepatotoxins and microbes.…”
Section: Introductionmentioning
confidence: 99%